Identification of the Genus Phyllanthus (Family Phyllanthaceae) in Southern Nigeria using Comparative Systematic Morphological and Anatomical Studies of the Vegetative Organs (Global Journal of Science Frontier Research, 2015)
Mull-Arg. and P. muellerianus (O. Ktze) Excel were compared using the morphology and anatomy with the view to adding to increasing the systematic lines of evidence and providing a more natural clarification than the existing one. The foliar and floral morphology of these species were described while the anatomical characteristics of the leaf, stem and root are valuable characters in delimiting the species. The results obtained from the studies showed that species of Phyllanthus have different attributes in their vascular characteristics that could be used together with other existing systematic evidence in clarifying the confusion in identifying these plants. Evidence from the nature of the palisade parenchyma in the mesophyll, nature of the collenchyma, sclerenchyma and vascular bundles are presented and discussed with their values in the systematic positions of these plants. A dichotomous bracketed key to the identification of the species studied is provided.
Keywords: phyllanthus species; morphology; anatomy; taxonomic evidence